Rebate subsidies, matching subsidies and isolation effects - Douglas D. Davis (Judgment and Decision Making, 2006)
In a series of recent experiments (Davis, Millner and Reilly, 2005, Eckel and Grossman, 2003, 2005a-c, 2006), matching subsidies generate significantly higher charity receipts than do theoretically equivalent rebate subsidies. This paper reports a laboratory experiment conducted to examine whether the higher receipts are attributable to a relative preference for matching subsidies or to an “isolation effect” (McCaffery and Baron, 2003, 2006). Some potential policy implications of isolation effects on charitable contributions are also considered.